Sky Cloning Project: Working with the Ethereal Beauty of the Space Nanomaterial Silica Aerogel - Michaloudis, Ioannis; Green, M. (Tsinghua University, 2012)
The Sky Cloning Project is an innovative, worldwide art & science project and its aim is the creation of sustainable works of art & design using the insulation medium of silica aerogel. Below are the principal properties of silica aerogel that make this exotic material applicable in the visual arts and design. These two properties and related artworks will be developed further in this paper: 天空克隆项目是一个全球领域性的，创新的艺术科学项目。该项目的目的是利用绝缘介质的二氧化硅气凝胶来创造可持续的艺术与设计作品。下面介绍的是两个二氧化硅气凝胶的属性，正因为有了此两项属性，才使得这个奇特的材料适用于视觉艺术和设计作品应用。关于该两项属性和相关的艺术作品，本文将在文中进行进一步发展性表述：Silica aerogel has an inherent blue & orange colouring - for the same reason the sky shares these colours. Each of these artworks exhibit the smokey blue colour, due to the phenomenon of Rayleigh scattering and the dark chaos behind Earth’s atmosphere. For particle sizes longer than a wavelength, Mie scattering predominates. Mie scattering is the reason the sunset is characterised by the gold orange hue, the same colour cast by the shadow of the aer( )sculptures. 象天空会产生蓝色和橙色, 二氧化硅气凝胶中蓝色和橙色的产生原因跟天空是一样的。每一个该类的艺术作品中自然呈现的烟熏蓝色, 是由于地球大气层背后的瑞利散射和黑暗混乱的现象而生成。对于大于波长的颗粒们, Mie散射占主导地位。Mie散射就是形成夕阳时散发金橙色色调的主要原因, 这跟AER () 雕塑的影子颜色是相同的。